A Mechanistic Cellular Atlas of the Rheumatic Joint - Zerrouk, Naouel; Aghakhani, Sahar; Singh, Vidisha; Augé, Franck; Niarakis, Anna (Frontiers in Systems Biology, 2022)
Rheumatoid Arthritis (RA) is a complex autoimmune disease of unknown aetiology. Its pathogenesis is suspected to arise from intricate interplays between signaling, gene regulation and metabolism. RA affects multiple cellular functions leading primarily to synovial inflammation, bone erosion and cartilage degradation in the patients' joints. Many different cells are implicated in the disease's onset and progression. The resident synoviocytes of macrophage and fibroblast types can interact with innate and adaptive immune cells and contribute to the disease's debilitating symptoms. A thorough, detailed, and mechanistic mapping of the molecular pathways and cell crosstalks and communications is essential to understanding the complex biological processes and the various disease manifestations. In this regard, we present the RA-Atlas, an SBGN-standardized, interactive, manually curated representation of molecular mechanisms involved in RA's pathogenesis. This state-of-the-art RA-Atlas includes an updated version of the global RA-map and cell-specific molecular interaction maps for CD4+ TH1 cells, fibroblasts, and M1 and M2 macrophages. Overall, the different molecular interaction maps were obtained by updating pre-existing maps (if available) with information extracted from literature (peer-reviewed articles) or pathway databases and enriched through differentially expressed genes or gene set enrichment analysis when needed. The maps are available on the standalone web server MINERVA (https://ramap.uni.lu/minerva/), allowing, among others, for visualization and navigation, cell-specific or experimental data overlay, gene set enrichment analysis, pathway export or drug query.